A General Viscous Model for Some Aspects of Tropical Cyclonic Winds - Pandey S.K.; Maurya J.P. (My University, 2025)
A previous investigation found that the existence of double exponential terms is a reason for rapid intensification of cyclonic winds with the assumption of a linearised form of viscosity. Here, we consider viscosity of general type and still get similar terms. A perturbation technique is applied to the solution. The domain of analysis is split into two regions: an inner one that experiences updraft, and an outer one that possesses no vertical component of velocity but does have azimuthal and radial components. It is observed that the radial pressure difference between an arbitrary radial distance and the point of the maximum wind diminishes with height, time, and Reynolds number. The azimuthal velocity, close to the ground, in region 1 increases fast with time, but its dependence diminishes at a height a little above the ground. At a considerable height, time ceases to be a factor, and further, above that, trends reverse. Perturbation terms behave almost identically with the terms without perturbation. The significance of their contribution depends on the magnitude of the Reynolds number and, hence, the viscosity. Trends for region 2 are qualitatively similar to those in region 1 but differ quantitatively. It is also observed that the central pressure drop decreases with time. © 2020 Walter de Gruyter GmbH, Berlin/Boston 2020.